Draft Annual Plan 1999-2000, Government of Mizoram - Planning Commission (Planning Commission, 1999)
In accordance with the 9th Five Year Plan priorities set by the Planning Commission, Govt.of India, the Government of Mizoram has given top most priority to the following : Agriculture and Allied activities and Rural Development with particular emphasis on self sufficiency in Food production., employment generation and eradication of poverty. Development of infrastructure, particularly Power and Road & Bridges The Ninth Plan also envisages to achieve 100% target by 2000AD in respect of the following Basic Minimum Services: 100% coverage of primary health services facilities in rural and urban areas.
Government of Mizoram
Government of Mizoram